The Influence of Knowledge, Sharia Compliance, Religiosity, and Local Wisdom on the Implementation of Green Banking Behavior - Febriza, Milla (Takaza Innovatix Labs Ltd., 2025)
This study examines how knowledge, sharia compliance, religiosity, and local wisdom influence green banking behavior among employees of Bank Muamalat in West Sumatra, Indonesia. While green banking is widely discussed in sustainable finance, few studies explore its behavioral drivers in Islamic banking, especially with religious and cultural integration. Using a quantitative approach, data were collected from 49 employees across four branches (Padang, Payakumbuh, Bukittinggi, Solok) through a structured questionnaire and analyzed with multiple linear regression (SPSS 26). The results show that knowledge (β = 0.234, p < 0.05), sharia compliance (β = 0.163, p < 0.01), religiosity (β = 0.212, p < 0.01), and local wisdom (β = 0.269, p < 0.001) each positively and significantly affect green banking behavior. Together, these variables explain 72.5% of its variance (R² = 0.725). This study is among the first to integrate behavioral, religious, and cultural dimensions in explaining green banking practices in Indonesia’s Islamic financial institutions. The findings highlight that cognitive, regulatory, spiritual, and cultural factors jointly shape environmentally responsible banking behavior. Islamic banks are encouraged to enhance training, reinforce sharia compliance, and integrate local wisdom into environmental programs to strengthen sustainable finance practices.